Work-time underemployment and financial hardship: class inequalities and recession in the UK - Warren, Tracey (Sage, 2015)
The economic crisis that led to recession in the UK in 2008–9 impacted in multiple ways on work and economic life. This article examines changes to the work-time of employees. The UK stood out for its recessionary expansion of work-time underemployment. Working in a job that provides ‘too few’ hours can have serious ramifications for the economic livelihood of workers. Working-class workers are central here. Drawing on analysis of large-scale survey data, the article identifies that workers in lower level occupations experienced the most substantial post-recessionary growth in the proportions working ‘too few’ hours. Did these work-time changes narrow or widen class inequalities in feelings of financial hardship? The article concludes that although middle-class workers also saw their financial positions damaged, this so-called ‘first middle-class recession’ did not erode class inequalities in financial hardship among UK workers.